شرط التحكيم في عقود الاستثمار الأجنبي " دراسة في القانون الليبي " - الجازوي سالمة فرج (Scientific Journal of University of Benghazi, 2021)
Investors seek to secure impartial and effective means of resolving disputes, and arbitration is seen as providing such a means. Unsurprisingly, it has grown to become the natural judiciary in this area. It assures the investors of resolving their disputes with the host state in a manner characterized by speed and secrecy, two attributes commensurate with the nature of investment contracts, and removed from this state’s own judiciary. Arbitration in disputes concerning investment contracts is, however, associated with a number of problems. A key problem stems from the fact that while the host state can in theory decide whether to agree to an arbitration clause, it finds itself in real life with no choice but to accept the clause. In studying the arbitration clause in foreign investment contracts, we adopted an analytical and critical approach and we reached several conclusions and recommendations. A key conclusion is that the inclusion of an arbitration clause in investment contracts encourages foreign investors to finance national projects; it assures them of a balanced position vis-à-vis the host state in case a dispute occurs. As might be expected, having such a clause has become commonplace in these contracts. Therefore, we call upon the Libyan legislature to enact a law to regulate arbitration in these contracts.